Interest rate pass through and asymmetries in retail deposit and lending rates: An analysis using data from Colombian banks (2015)
Using a sample of Colombian banks, we examine retail interest rate adjustment in response to changes in wholesale interest rates. Interest rate pass through running from wholesale to retail rates is found to be both partial and heterogeneous across banks. This suggests that the effectiveness of monetary policy is limited. Further investigation reveals that the behaviour of retail deposit rates appears consistent with collusive behaviour between banks insofar as interest rates are more rapidly adjusted downwards than upwards. In the case of retail lending rates, it appears that banks more rapidly reduce than increase rates. This suggests that expansionary monetary policy in Colombia may be relatively more effective than contractionary policy. © 2015 Elsevier B.V.